ANALISIS MIKROSATELIT PADA SAMPEL FESES GAJAH SUMATERA (Elephas maximus sumatranus) DI TAMAN NASIONAL TESSO NILO, RIAU - Beno Fariza Syahri; Haris Gunawan; Herawati Sudoyo (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Sumatran elephant (Elephas maximus sumatranus) is  an  endemic  land mammal on Sumatra  Island which  now  is  on  critically endangered. The population of Sumatran elephant in Riau Province spread in 9 pouches of population,  one of them is population in  Tesso  Nilo National Park (TNNP).  Habitat fragmentation and  land  conversion  in protected areas caused  condition of Sumatran elephant’s population had  deteriorated. Therefore, we need a precise conservation effort  to save the population of  Sumatran elephant in TNNP. These  efforts  require  appropriate  information on the number of individuals and population genetic. The aims of this study were to determine the number of individuals, variation and frequency  of allele, and  the  level of heterozygosity of Sumatran elephant population in TNNP based on genetic information.  Molecular analysis using microsatellite marker was performed on 108 non-invasive samples which were collected using CMR method. The result revealed that there were 73 individuals of Sumatran elephant in TNNP.  The average number of allele  variation  from 13 microsatelite loci  which were  analized was 2.85 allele/locus  with average observed heterozygosity (0.507)  is higher than  expected heterozygosity  (0.490). Those  indicates that allele frequencies found to be above of the Hardy-Weinberg equilibrium. This studyproved that there is no genetic pressure of Sumatran elephant population in TNNP.